Multiscale spatio-temporal feature fusion based non-intrusive appliance load monitoring for multiple industrial industries - Lin, Lin; Liu, Jiang; Huang, Nantian; Li, Shilin; Zhang, Yunshan (Applied soft computing, 2024)
The appliance types and power consumption patterns vary greatly across different industries. This can lead to unstable identification results of traditional appliance load monitoring methods in different industries. A non-intrusive appliance load monitoring (NIALM) method for multiple industries based on multiscale spatio-temporal feature fusion has been proposed. Firstly, the ConvNeXt Block with efficient channel attention has strong feature extraction capability. Spatial features of appliance state changes and micro-variations generated during operation can be extracted from mixed industrial load information by it. Meanwhile, the bidirectional gated recurrent neural network is used to learn the bidirectional dependencies of the load data, obtaining temporal features. Then, the multi-scale feature extraction module is used to extract temporal and spatial features from different depths of the network layers. And the extracted multi-scale temporal and spatial features are fully integrated. Finally, the proposed model is optimized using the Stochastic Weight Averaging method. During the training process, a certain number of model weights are randomly averaged, which can improve the model's generalization ability and identification accuracy. The experiment was conducted on six different industries. The evaluation indexes such as accuracy, F1 score, and Wasserstein distance are also used to verify the effectiveness and superiority of the method. •Designs a multiscale spatio-temporal feature fusion model for multi-industry NIALM.•The improved ConvNeXt module are designed to extract spatial features efficiently.•The Stochastic Weight Averaging improves model generalization.